Considerations when using rating scales to support teacher professional development: A commentary on Weadman, Serry and Snow (2022). Issue 4 (August 2022) - Mathers, Sandra J.
While observational rating scales such as the Emergent Literacy and Language Early Childhood Checklist for Teachers (ELLECCT) have potential to support Early Childhood Teachers in improving their practice, the existence of a valid and reliable tool is no guarantee of success. A carefully constructed model of teacher professional development will be required to ensure benefits for instructional practice and child language outcomes. This commentary considers the evidence available to guide intelligent design of such a model.